Heavy Metals Concentrations in the Shell and Tissue of Periwinkle (Tympanotonus fuscatus) and Giant Land Snail (Achatina fulica) in Soku Community of Niger Delta, Nigeria. - C.I.A., Nwoko; L.N., Ukiwe (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The pollution of aquatic ecosystem by heavy metals has assumed serious proportions due to their toxicity and accumulative behaviour. River dams are especially at risk of contamination by different contaminants from anthropogenic sources including heavy metals since change of sediment regime often occur. The accumulation of five heavy metals; chromium (Cr), Cadmium (Cd), Lead (Pb), Copper (Cu) and Arsenic (As) in periwinkle, (Tympanotonus fuscatus, var, radula) and giant land snail (Achatina fulica) shell and soft tissue collected from Soku Community, Akuku-toru Local Government Area of Rivers State, Nigeria. The periwinkle and giant land snail were processed and analyzed for heavy metals presence. Results obtained showed that the periwinkles accumulated more of these heavy metals than the snails. Copper and arsenic were the highest concentrated heavy metals in the periwinkle shell soft tissue. The concentration of copper and arsenic in periwinkles soft tissue was found to be l,612 mg/kg and 2.40 mg/kg respectively. In the giant land snail the soft tissue concentrated more of copper (277 mg/kg). These values exceeded set standards for guidelines on toxicity.